2018
DOI: 10.1371/journal.pone.0203813
|View full text |Cite
|
Sign up to set email alerts
|

HDL inflammatory index correlates with and predicts severity of organ failure in patients with sepsis and septic shock

Abstract: ObjectiveHigh density lipoprotein (HDL) is important for defense against sepsis but becomes dysfunctional (Dys-HDL) during inflammation. We hypothesize that Dys-HDL correlates with organ dysfunction (sequential organ failure assessment (SOFA) score) early sepsis.MethodsA prospective cohort study of adult ED sepsis patients enrolled within 24 hours.ResultsEighty eight patients were analyzed. Dys-HDL (expressed as HDL inflammatory index (HII)) correlated with SOFA at enrollment (r = 0.23, p = 0.024) and at 48 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 33 publications
3
70
0
Order By: Relevance
“…A screening lipid panel will be drawn and paid for by the study prior to enrolment to ensure that patients meet the requirement of total cholesterol ≤100 mg/dL or HDL-C + LDL C ≤70 mg/dL. This cut-off is based on preliminary studies that suggest that patients at increased risk of adverse outcomes from sepsis who may respond to cholesterol stabilisation have low enrolment cholesterol levels 22 28 29. Our data also show that nearly 50% of patients with sepsis with SOFA score ≥4 meet the proposed screening cholesterol criteria.…”
Section: Methods and Analysismentioning
confidence: 95%
See 2 more Smart Citations
“…A screening lipid panel will be drawn and paid for by the study prior to enrolment to ensure that patients meet the requirement of total cholesterol ≤100 mg/dL or HDL-C + LDL C ≤70 mg/dL. This cut-off is based on preliminary studies that suggest that patients at increased risk of adverse outcomes from sepsis who may respond to cholesterol stabilisation have low enrolment cholesterol levels 22 28 29. Our data also show that nearly 50% of patients with sepsis with SOFA score ≥4 meet the proposed screening cholesterol criteria.…”
Section: Methods and Analysismentioning
confidence: 95%
“…Our study proposes to carefully select for potential responders and metabolisers of LIE by only enrolling patients with low baseline total cholesterol (<100 mg/dL) and by excluding patients with severe liver dysfunction (total bilirubin >2 mg/dL or albumin <1.5 g/dL). Importantly, these screening criteria will still allow enrolment of nearly half of patients with sepsis based on our previous observational studies 28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that, depending on the protein and lipid composition, HDL can develop an anti-inflammatory or an inflammatory profile [27, 28]; it is also well known that both infection and sepsis decrease the plasma levels of HDL in patients [29, 30]. HDL with an inflammatory profile is related to SOFA score [31] and elder patients with sepsis were reported to present with a lower cholesterol efflux capacity, which is the main function of HDL, and a higher HDL inflammatory index [32].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrate that low cholesterol levels (specifically LDL-C) may increase sepsis risk. [4, 29] Barter, et al found that CETP inhibitors lead to drastic elevations in HDL, reductions in LDL, and increased all-cause mortality. ; death from infection comprised nearly half of the deaths.…”
Section: Discussionmentioning
confidence: 99%